Effects of Alternative Wrist Grip Techniques on Pain, Strength, and Function in the Wrists of Novice Weightlifters - Muhammad Usama; Saba Riaz; Muhammad Muzammil; Ahmer Ali; Ayesha Noor (Revista de Investigación e Innovación en Ciencias de la Salud)
Introduction. The wrist, with its composite anatomical composition, is deemed the most complex joint in the human body, vital for multifaceted hand movements. However, diseases or injuries can significantly impair wrist function, necessitating a comprehensive understanding of its anatomy and biomechanics. Concurrently, weightlifting, a popular exercise regimen, demands precise wrist functionality for optimal performance.